Georgia Architectural and Historic Properties Survey of Rural [106] South west section of county, Quitman, Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Rural [106] South west section of county, Quitman, Ga. December 1980. Large 1 story rectangular house with gabled tin roof. Square posts support shed porch. Interior chimney. Double hung sash windows with 3/1 lights. Set on brick piers. Fair condition. Date of Construction: c. 1915. Typical common rural house.
Georgia Architectural and Historic Properties Survey of Rural [106] South west section of county, Quitman, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 1 scan. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 821 KB (841,182 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Lowndes Co. (Ga.); Quitman (Ga.)